Kebutuhan Mahasiswa Asing KNB (Kemitraan Negara Berkembang) dalam Pembelajaran BIPA Di UPT Bahasa UNS Surakarta (The Needs of Foreign Students in BIPA Learning at UPT Bahasa UNS Surakarta) - Widhayani, Arrie (Balai Bahasa Jawa Tengah, 2019)
This study aims to describe the needs of foreign students in BIPA learning at UPT Bahasa UNS Surakarta. The subjects of this study were foreign students of the KNB program (Developing Country Partnership). Data collection with questionnaires, interviews and documentation. The results of the study show that in general foreign students consider BIPA learning to be very helpful in academic fluency and communication. In addition, for foreign students BIPA learning also integrates Indonesian culture and language so that they consider the introduction of Indonesian culture to make it easier to learn Indonesian.